Pelaksanaan Program Kegiatan Keagamaan dalam Menumbuhkan Karakter Religius Siswa SMP Negeri 1 Jenangan - Arif Rahman Hakim; Amalia Alfitrianingrum; Fadeli Ehsan Hanafi; Sahidin Sahidin; Yerin Tri Agustina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2022)
The development of religious character in schools is part of an important program that needs to be implemented in guiding and directing students to have good attitudes and behaviors. The purpose of this research is to investigate the Implementation of the Religious Activity Program in Growing the Religious Character of SMPN 1 Jenangan Students.. The descriptive qualitative method was used in this study. The results showed that in growing the religious character of students at SMP Negeri 1 Jenangan, it was implemented through the implementation of a religious activity program involving all components of the school such as the principal, teachers and employees. The religious activity programs carried out at SMP Negeri 1 Jenangan are dhuha prayers, dhuhur prayers, kultum dzuhur, tahiyyatul masjid prayers, murattal juz 'amma before PAI learning, and tahfidz Qur'an. The implementation of religious programs is carried out routinely to familiarize students with carrying out religious activities. The implementation of this religious activity program had a good impact on the formation of students' religious character, based on the results of the questionnaire distribution, it was found that 63% of students stated that religious activity programs had a significant impact on their religious attitudes and behavior.